Corticosteroid Administration to Prevent Complications of Anterior Cervical Spine Fusion: A Systematic Review. Issue 3 (May 2018) - Zadegan, Shayan Abdollah; Jazayeri, Seyed Behnam; Abedi, Aidin; Bonaki, Hirbod Nasiri; Vaccaro, Alexander R.; Rahimi-Movaghar, Vafa
Study Design: Systematic review. Objectives: Anterior cervical approach is associated with complications such as dysphagia and airway compromise. In this study, we aimed to systematically review the literature on the efficacy and safety of corticosteroid administration as a preventive measure of such complications in anterior cervical spine surgery with fusion. Methods: Following a systematic literature search of MEDLINE, Embase, and Cochrane databases in July 2016, all comparative human studies that evaluated the effect of steroids for prevention of complications in anterior cervical spine surgery with fusion were included, irrespective of number of levels and language. Risk of bias was assessed using MINORS (Methodological Index for Non-Randomized Studies) checklist and Cochrane Back and Neck group recommendations, for nonrandomized and randomized studies, respectively. Results: Our search yielded 556 articles, of which 9 studies (7 randomized controlled trials and 2 non–randomized controlled trials) were included in the final review. Dysphagia was the most commonly evaluated complication, and in most studies, its severity or incidence was significantly lower in the steroid group. Although prevertebral soft tissue swelling was less commonly assessed, the results were generally in favor of steroid use. The evidence for airway compromise and length of hospitalization was inconclusive. Steroid-related complications were rare, and in both studies that evaluated the fusion rate, it was comparable between steroid and control groups in long-term follow-up. Conclusions: Current literature supports the use of steroids for prevention of complications in anterior cervical spine surgery with fusion. However, evidence is limited by substantial risk of bias and small number of studies reporting key outcomes.